Nutritional and lifestyle management of the aging journey: A narrative review - Kassis, Amira; Fichot, Marie-Claire; Horcajada, Marie-Noelle; Horstman, Astrid M. H.; Duncan, Peter; Bergonzelli, Gabriela; Preitner, Nicolas; Zimmermann, Diane; Bosco, Nabil; Vidal, Karine; Donato-Capel, Laurence (Frontiers in Nutrition, 2023)
With age, the physiological responses to occasional or regular stressors from a broad range of functions tend to respond and adjust more slowly and restoring these functions in the normal healthy range becomes increasingly challenging. Even if this natural decline is somehow unavoidable, opportunities exist to slow down and attenuate the impact of advancing age on major physiological processes which, when weakened, constitute the hallmarks of aging. This narrative review revisits the current knowledge related to the aging process and its impact on key metabolic functions including immune, digestive, nervous, musculoskeletal, and cardiovascular functions; and revisits insights into the important biological targets that could inspire effective strategies to promote healthy aging.